PPAR-gamma regulates PFAS-mediated proinflammatory cytokines in lung epithelial cells - Shaikh, Sadiya Bi; Faizan, Md Imam; Islam, Khursheed Ul; Rehan, Virender K.; Rahman, Irfan (Frontiers in Pharmacology, 2026)
BackgroundPer and polyfluoroalkyl substances (PFAS), including the legacy compound perfluorooctanesulfonic acid (PFOS), are persistent organic pollutants with long biological half-lives. Emerging evidence suggests a significant accumulation of PFAS/PFOS in the human lung, potentially contributing to inflammation and altered immune responses. However, the role of peroxisome proliferator-activated receptor gamma (PPARγ) signaling in PFAS/PFOS-induced pulmonary toxicity remains unclear.MethodsPrimary human bronchial epithelial (NHBE) cells were exposed to 15 µM binary PFAS mixture (PFOS + PFOA) or quaternary mixture (PFOS, PFOA, PFHxS, GenX) with or without the PPARγ antagonist (15 µM) and/or the PPARγ agonists rosiglitazone (10 µM) or pioglitazone (10 µM) for 24 h. BALB/c mice were orally administered PFOS (2 mg/kg/day) or vehicle control for 2 weeks.ResultsIn NHBE cells, PFAS exposure significantly increased IL-6 and IL-8 secretion. Treatment with rosiglitazone or pioglitazone reversed these cytokine increases, whereas co-treatment with the PPARγ antagonist elevated IL-6 and IL-8 levels compared to PFAS exposure alone in epithelial cells. PFOS exposure in mice caused a reduction in lung PPARγ protein levels, while PPARα expression remained unchanged.ConclusionThese findings demonstrate that PFAS-induced pro-inflammatory cytokines is mediated, at least in part, through PPARγ signaling, and that pharmacological activation of PPARγ signaling can attenuate PFAS-triggered pro-inflammatory cytokine responses in lung epithelial cells.